(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
In the present study, an effort is made to blend Eri-silk fibre with jute in different blended ratios (Eri-silk: Jute ratios of 100/0; 75/25, 50/50, 25/75 and 0/100) to develop a range of blended yarns. These yarns arethen used as weft yarn to produce a value-added woven textile of plain weave design, while keeping the cotton yarn in the warp direction. The resulting fabrics are evaluated comprehensively to identify the blend ratio that provides superior physical, mechanical and comfort-related properties. Areal density, thickness, crease recovery angle, stiffness, tensile and tearing strengths, elongation percentage, cover factor, water wicking, air permeability and drapability are assessed in detail. Based on the findings,theEri-silk: jute (75/25) blend is observed to exhibit the most favourable overall performance across the tested parameters. Different apparel textile products arealso developed from blended fabrics, demonstrating their potential for functional and aesthetic applications.